Response of Amaranthus cruenthus to Different Aeration Methods and Varying Irrigation Levels - Sadiku, Isiaka; Yusuf, K. O.; Ogunlela, A. O. (Indonesian Journal of Agricultural Research, 2022)
Response of Amaranthus cruenthus to varying aeration methods (aeration of irrigation water (A1), air injection to crop root zone in soil before irrigation (A2), air injection to crop root zone in soil after irrigation (A3), and non aeration treatment (A0)) and irrigation levels (100% field capacity (FC) (W0), 75% FC (W1), 65% FC (W2) and 55 % FC (W3) were investigated. The results showed that varying irrigation as well as aeration levels had significant effects on the height of A. cruenthus while no significant difference was obtained in number of leaves across the field capacities during the growing period. The findings of this work showed that A. cruenthus was not sensitive to air treatment as expected. This is because lower number of leaves were obtained when air was either injected into the soil before or after irrigation as well as when air was injected into irrigation water at 4 and 7 weeks after planting. Plant height was maximum when no air was introduced to the plant at 4 Weeks After Planting. However, the number of leaves were highest at 65% FC throughout the growing period. The shoot, root and whole plant fresh weight were all significantly influenced by the aeration treatments but not FC except the root fresh weight. The edible yield (shoot fresh weight) was highest (48.55g) at 100% FC (W0). Also, when the irrigation water was injected with air (A1), the highest edible yield of 57.33 g was obtained. The highest Water Use Efficiency was exhibited at 100% FC (W0) while aeration of irrigation water (A1) gave the highest (26.06) Air Use E. 65% field capacity is best for planting A. cruenthus without negatively affecting the yield. Â